UNDERSTANDING THE IMPACT OF DIGITAL BEHAVIOR ON SKINCARE PURCHASES - Sylvia Samuel; Daniel Widjaja (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2025)
Social media interactions in the rapidly evolving digital marketplace increasingly shape consumer purchasing behavior. This study investigates the influence of Electronic Word of Mouth (e-WOM) and price perception on purchase intention, with brand image as a mediating variable, using the Indonesian skincare brand Skintific as a case study. Utilizing a quantitative approach with Structural Equation Modeling (SEM) on data from 372 TikTok users in West Jakarta, the findings reveal that e-WOM significantly impacts purchase intention but does not significantly affect brand image. Conversely, price perception exerts a strong influence on brand image and, indirectly, on purchase intention. Brand image significantly mediates the relationship between independent variables and purchase intention. These insights suggest that while e-WOM remains essential for influencing immediate purchasing decisions, price perception plays a more substantial role in shaping brand image, which drives long-term consumer loyalty. The study contributes to digital marketing literature by highlighting the nuanced interplay between user-generated content, pricing strategies, and consumer behavior in social commerce.